The Association of Acute and Chronic Postpartum Pain with Postpartum Depression in a Nationally Representative Sample of Canadian Women - Gaudet, Caroline (Université d'Ottawa / University of Ottawa, 2011)
The association between pain and depression is well documented across various populations, but not in puerperal women. This study examined the association of childbirth pain with postpartum depression (PPD) in a nationally representative sample of Canadian women. Data from the Canadian Maternity Experiences Survey (n=6421) was used. Multivariate logistic regressions and partial proportional odds models were fitted and included socio-demographic, obstetric, health, psychological, and psychosocial factors. Chronic pain sufferers at mean 7.3 months postpartum had adjusted odds of PPD of 2.4 (95% CI: 1.6, 3.6) compared to women without pain. Adjusted odds of PPD increased with the number of areas of chronic pain, reaching 4.2 (95% C.I.: 0.7, 25.0) for 3 or more areas. Immigration, obesity, cesarean section and social support increased the strength of the association while smoking and the use of pain relief were protective effect modifiers. Persistent postpartum pain is a major risk factor for PPD.
Keywords: Pospartum Depression; Chronic pain; Childbirth; Maternal Health; Risk factors